Uncommon pancreatic tumor - a case report (Bangladesh Journal of Pathology, 2011)
Keywords: uncommon pancreatic cancer; anaplastic carcinomaDOI: http://dx.doi.org/10.3329/bjpath.v26i1.9151 BJPATH 2011; 26(1): 39-40